Sorption-Desorption, Degradation and Leaching of Napropamide in Selected Malaysian Soils - Sadegh Zadeh, Fardin (2010)
Sorption, degradation and leaching are the important processes affecting fates of pesticides in the soil environment. Sorption influences the magnitude of the other processes and is considered to be one of the major processes affecting the interactions occurring between pesticides and the solid phase in the soil environment. Dissipation of pesticides can occur by degradation and leaching. There is no reported study on napropamide fates in Malaysian soils or even in tropical soils. Napropamide is one of the pre-emergence herbicides used to control several grasses and broadleaf weeds in tobacco and kenaf fields in Malaysia. Sorption-desorption, degradation and leaching of napropamide were studied in selected Malaysian soils and Baging soil amended with chicken dung (CD) and palm oil mill effluent (POME). The ability of a UV-spectrophotometry to determine napropamide concentration in soil sorption study was studied as well. Results showed that UV-spectrophotometry method was as reliable as the HPLC in determining napropamide concentration in the supernatant of batch equilibrium sorption study. Interference by dissolved organic carbon in the napropamide determination by the spectrophotometer method could be easily corrected using a dual beam spectrophotometer. Baging soil has very low affinity for napropamide. The sorption capacity (Kf) of Baging soil and Baging soil amended with 80 Mg ha-1 CD and POME were 0.22, 41.6 and 3.96, respectively. Dissolved organic carbon (DOC) derived from CD or POME did not affect sorption capacity of amended Baging soil. The sorption capacities of the selected Malaysian soils for napropamide were in the following order: Linau (Kf = 66.2) > Teringkap (Kf = 56) > Gunung Berinchang (Kf = 43) > Jambu (Kf = 26) > Rudua (Kf = 8) > Baging soil (Kf = 0.22). The results indicated that sorption increased with increasing clay and organic carbon content (OC) of the soils. Among the BRIS soils studied, the Baging which has the lowest organic matter and clay content, also has the lowest Kf. Napropamide half-life was lowest in the Baging soil (43 d) and its half-life was increased to 69 (d) and 49.5 (d) with the addition of 20 Mg ha-1 CD and POME, respectively. Degradation of napropamide decreased in Baging soil receiving DOC derived from CD and POME. The shortest and longest half-lives among the selected Malaysian soils were observed in Baging (43 d) and Linau soil (100 d), respectively. The results indicated that napropamide degradation decreased with the increasing soil sorption capacity. Napropamide was leached out earlier in the Baging soil as compared to the other soils. The results showed that soils which have low sorption capacities for napropamide leached napropamide earlier from the soil column. On the other hand, for Linau soil which had the highest sorption capacity for napropamide (Kf = 66.2), no napropamide was detected in the leachate even after seven pore volumes of effluent water. The results also suggested that DOC did not affect the leaching of napropamide. Overall, application of napropamide in the selected Malaysian soils would not pose a threat to the environment especially the groundwater except in soil with low organic matter and clay content, and high hydraulic conductivity such as the Baging soil.